2003
DOI: 10.4269/ajtmh.2003.68.413
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Chloroquine Sensitivity and Low Prevalence of the Plasmodium Falciparum Chloroquine Resistance Transporter Gene Mutation K76t Following the Discontinuance of Chloroquine Use in Malawi

Abstract: In 1993, Malawi stopped treating patients with chloroquine for Plasmodium falciparum malaria because of a high treatment failure rate (58%). In 1998, the in vitro resistance rate to chloroquine was 3% in the Salima District of Malawi; in 2000, the in vivo resistance rate was 9%. We assayed two genetic mutations implicated in chloroquine resistance (N86Y in the P. falciparum multiple drug resistance gene 1 and K76T in the P. falciparum chloroquine resistance transporter gene) in 82 P. falciparum isolates collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
98
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(112 citation statements)
references
References 18 publications
11
98
3
Order By: Relevance
“…Nevertheless, our observations are consistent with recent findings in parts of China (Liu et al, 1995), Vietnam (Nguyen et al, 2001;Thanh et al, 2001;Nguyen et al, 2003) and Malawi (Kublin et al, 2003;Mita et al, 2003;Mita et al, 2004), where concerted efforts to halt CQ use have resulted in an increase in the in vitro and in vivo sensitivity of field isolates to the drug, and a concomitant decrease in the prevalence of certain mutations in pfmdr1 and pfcrt associated with resistance. It was shown in Malawi (Kublin et al, 2003) that the frequency of the KAET mutation at codon 76 of pfcrt found in most [but not all Rason et al, 2002;Thomas et al, 2002;Vinayak et al, 2003)] strains resistant to CQ in vitro declined sixfold from 1992 to 2000.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Nevertheless, our observations are consistent with recent findings in parts of China (Liu et al, 1995), Vietnam (Nguyen et al, 2001;Thanh et al, 2001;Nguyen et al, 2003) and Malawi (Kublin et al, 2003;Mita et al, 2003;Mita et al, 2004), where concerted efforts to halt CQ use have resulted in an increase in the in vitro and in vivo sensitivity of field isolates to the drug, and a concomitant decrease in the prevalence of certain mutations in pfmdr1 and pfcrt associated with resistance. It was shown in Malawi (Kublin et al, 2003) that the frequency of the KAET mutation at codon 76 of pfcrt found in most [but not all Rason et al, 2002;Thomas et al, 2002;Vinayak et al, 2003)] strains resistant to CQ in vitro declined sixfold from 1992 to 2000.…”
Section: Discussionsupporting
confidence: 93%
“…In Vietnam, where artemisinin replaced CQ as the first-line treatment for falciparum malaria in 1992, comparative studies have shown that in vitro and in vivo parasite sensitivity to CQ has increased significantly over time (Nguyen et al ., 2001;Thanh et al ., 2001;Nguyen et al ., 2003). A field survey in Malawi, where sulfadoxinepyrimethamine replaced CQ as the first-line antimalarial in 1993, showed that in vitro chloroquine resistance in the local area had decreased from 47% in 1988 to 3% in 1998, noting this was also accompanied by a significant reduction in the prevalence of one of the key pfcrt mutations associated with resistance (Mita et al ., 2003). This was subsequently shown to be attributed to expansion of the wild-type pfcrt allele in the parasite population, rather than a back mutation in the mutant allele (Mita et al ., 2004).…”
Section: Introductionmentioning
confidence: 99%
“…This mutation in a putative transporter gene is well-associated with chloroquine resistance in P. falciparum (5). The MSS-HTA was compared with a standard allele-restricted PCR (ARPCR) in clinical samples from Malawi, a country where standard PCR analyses and a recent clinical trial have suggested that chloroquine-resistant malaria has disappeared (6)(7)(8)(9).…”
mentioning
confidence: 99%
“…Previous studies have reported the reversal of the wild type (K76) genotype after cessation of CQ use (29,30). Although the current study was not aimed at exploring this phenomenon, the persistence of the T76 mutant phenotype was detected in a geographic region where use of CQ for falciparum malaria (but not vivax malaria) was abolished 21 years ago.…”
Section: Discussionmentioning
confidence: 75%